The Pengaruh Metode Pengeringan Kering Angin dan Oven Terhadap Karakteristik Simplisia Bunga Kecombrang (Etlingera elatior) - Fardi, Audry Regita Ayu; Raharjo, Sentot Joko (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022), 2022)
Drying is one of the post-harvest processes that can affect the quality standard of kecombrang flower simplicia. The purpose of this research is for determine the effect of wind and oven drying methods on the characteristics of kecombrang flower simplicia. This research method includes the manufacture of kecombrang flower simplicia by using wind and oven drying methods, as well as characteristic testing including organoleptic, macroscopic, microscopic, water content, water soluble extract content, ethanol soluble extract content, thin layer chromatography, and total flavonoid content. The results showed that kecombrang flower simplicia on wind and oven drying met the requirements which included several parameters organoleptic, microscopic, macroscopic, moisture content, water soluble extract content, total flavonoid content. In the oven drying process, the simplicia of kecombrang flower produced the best characteristics organoleptic, macroscopic, moisture content and total flavonoid content, while in wind drying the extract showed the highest water soluble and ethanol content. The conclusion of this research is that there is an effect between the wind and oven drying methods on the characteristics of kecombrang flower simplicia which include water content, water soluble extract content, and total flavonoid content.